Are Cosmetic Procedures Comparable to Antidepressive Medication for Quality-of-Life Improvements? A Systematic Review and Controlled Meta-Analysis - Rudolph, Christina; Hladik, Casey; Stroup, Donna F.; Frank, Konstantin; Gotkin, Robert H.; Dayan, Steven H.; Patel, Ashit; Cotofana, Sebastian (Facial Plastic Surgery, 2019)
Cosmetic procedures, especially cosmetic minimally invasive treatments, are rising in popularity, despite societal perception that these procedures may not improve patient health. The purpose of this study was to conduct a systematic review and controlled meta-analysis to compare the effects of cosmetic procedures and antidepressant treatment on health-related quality-of-life improvement. The PubMed database was queried in two independent searches to identify peer-reviewed cosmetic and antidepressant articles published between 1996 and 2017 that prospectively assessed the impact of the treatment on quality of life. All results were screened using defined exclusion and inclusion criteria and data were extracted using a standardized protocol. The meta-analysis was performed using a random-effects model. Five of 2,788 cosmetic studies and eight of 2,312 antidepressant studies met all inclusion criteria and utilized the 36-Item Short Form Health Survey (SF-36) measure. Except for the physical functioning scale, when compared with the cosmetic studies, antidepressant studies had significantly lower median baseline and post-treatment follow-up scale scores with larger median score improvement (p < 0.05). Positive effect sizes following treatment were observed for all eight SF-36 scales (range: 0.32–1.16; p < 0.05). This meta-analysis provides evidence that cosmetic procedures objectively improve a patient's health-related quality of life. While antidepressant studies exhibited greater SF-36 score improvement except for the physical functioning scale, both treatment groups demonstrated the greatest improvement in mental health and role emotional scales. As previously suggested, a disconnect exists between score improvement and clinical improvement due to baseline severity, ceiling effect, and regression to the mean effects.
Keywords: quality of life; aesthetic surgery; cosmetic surgery; antidepressant therapy; SF-36